There Is No Alternative to Cartography - Williams, Edwin (Regimes of Derivation in Syntax and Morphology, 2011)
In modern grammatical thinking, a clause has a "Functional Structure" (F-structure), a spine consisting of some number of non-lexical heads, perhaps as many as 150, with the lexical verb at the bottom. If we number these heads 0,...n and reserve 0 for the lexical head, then a clause is a sequence Fn...F0. If we embed a clause beneath a lexical verb, as in (1), we have two F-structures, and we have a boundary between them, the "Fn/F0 boundary," circled here: (1